Multiple brain metastases from mucoepidermoid carcinoma of the parotid gland: case report and review of the literature - Yao Christian Hugues Dokponou; Fresnel Lutèce Ontsi Obame; Moussa Elmi Saad; Mandour Cherkaoui; Mohamed Reda El Ochi; Housni Abderrahmane; Abad Chérif El Asri; Miloudi Gazzaz (Egyptian Journal of Neurosurgery)
Abstract Background Brain metastases from Mucoepidermoid carcinoma (MEC) of the parotid gland is extremely rare. To our best knowledge, this is the second report of BM from MEC of parotid gland. Case presentation We report the case of a 61-year-old man who was surgically treated for mucoepidermoid carcinoma classified as T3N1M0 and was admitted because of multiple brain metastases from this tumor. He underwent surgery for cerebellar metastases and underwent adjuvant radiotherapy. Conclusion In this article, the authors report a case of brain metastases from parotid MEC treated by resection and radiation therapy. A review of the literature did not reveal any other cases of this type.